Digital Booklet as a Training Tool for First Aid for Ankle Injuries - Pria Wahyu Romadhon Girianto; Melani Kartikasari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Ankle injuries are a common occurrence among students, particularly due to high levels of physical activity. The recommended initial treatment is the R.I.C.E. method, which stands for rest, ice, compression, and elevation. This study aims to analyze the impact of educational interventions using digital booklets on enhancing PMR students' ability to administer first aid for ankle injuries according to the R.I.C.E. method. The study employed a pre-experimental design featuring a one-group pre-test and post-test format. The population consisted of all PMR members at SMK Ahmad Yani Gurah Kediri, totaling 28 respondents selected through total sampling. The educational intervention took place over three sessions, each lasting 120 minutes, during which digital booklets were utilized. These booklets contained educational content, visual aids, and step-by-step instructions for applying the R.I.C.E. procedure. Data were gathered using psychomotor observation sheets and analyzed with the Wilcoxon Signed Rank Test. Findings revealed a significant improvement in the students' abilities; the average pre-test score rose from 44% to 82%, with a p-value of 0.000 (p ≤ 0.05). Prior to the digital booklet intervention, the PMR students' abilities were categorized as poor, reflecting limited knowledge and practical skills in first aid. Following the intervention, their abilities improved to a satisfactory level, demonstrated by their correct and sequential execution of the R.I.C.E. method. In conclusion, the use of digital booklets effectively enhanced PMR students' skills in administering first aid for ankle injuries using the R.I.C.E. method, thereby supporting the development of practical skills within the school environment.